Management of human talent and labor competences in teachers of public educational institutions - Quiroz Noriega, Gloria Elizabeth (2019)
The main objective of the present investigation was focused on establishing whether the management of human talent and the labor competencies of teachers are linked to each other. For this reason, we work with a quantitative approach and a non-experimental design of a correlational level. The sample of probabilistic order was composed of 196 teachers of the Learning Network Nº 1 of the Ventanilla district, who were administered two measuring instruments: the Inventory of human talent management of Estrella Quispealaya was used and Manuel Torres and the inventory of teaching labor competencies of the Ministry ofEducation of Mexico. The data that was collected was processed using the statistical package SPSS version 25 and specifically the Spearman rho. The results indicate that both variables are significantly related (r= 0.80). Likewise, it was found that the diverse dimensions of human talent management are linked to the diverse labor competencies of teachers.